Driver circuit for a PAM‐4 optical transmitter using 65 nm CMOS and silicon photonic technologies. Issue 23 (1st November 2016) - Zhou, S.; Wu, H.; Sadeghipour, K.; Scarcella, C.; Eason, C.; Rensing, M.; Power, M.; Antony, C.; O'Brien, P.; Townsend, P.; Ossieur, P.
Abstract : A push–pull silicon photonic Mach–Zehnder modulator (MZM) driver is presented which uses a switched capacitor approach to generate a ∼2 V peak‐to‐peak differential 4‐level pulse amplitude modulation (PAM‐4) signal. The driver chip includes a Gray encoder and retiming flip‐flops. The switched capacitor approach allows driving the lumped silicon photonic MZM with reduced power consumption compared with the conventional approach of driving MZMs (with transmission line based electrodes) with a power amplifier. This is critical for upcoming short‐reach link standards such as 400 Gbit/s 802.3 Ethernet. The chip was fabricated using a 65 nm CMOS technology and flip‐chipped on top of the silicon photonic chip (fabricated using IMEC's ISIPP25G technology) that contains the MZM. Open eyes with 4 dB extinction ratio for a 36 Gbit/s (18 Gbaud) PAM‐4 signal are experimentally demonstrated. The electronic driver chip has a core area of 0.11 mm 2 and consumes 236 mW from 1.2 to 2.4 V supply voltages. This corresponds to an energy efficiency of 6.55 pJ/bit including Gray encoder and retiming, or 5.37 pJ/bit for the driver circuit only.